The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4269/ajtmh.2011.11-0134
|View full text |Cite
|
Sign up to set email alerts
|

Severity Predictors in Eschar-Positive Scrub Typhus and Role of Serum Osteopontin

Abstract: We prospectively evaluated severity predictors in terms of host, microorganism, and treatment factors in 153 eschar-positive scrub typhus patients. Severity was assessed with the Acute Physiology and Chronic Health Evaluation (APACHE) II score (< 10 versus ≥ 10) and predefined criteria of severe complications. Genotypes of Orientia tsutsugamushi were determined. Independent risk factors for severity (APACHE II score ≥ 10) were old age, diabetes mellitus, serum osteopontin > 100 ng/mL, and a group of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(55 reference statements)
3
17
0
Order By: Relevance
“…Although the Gilliam and Karp serotypes are reportedly more common in the central part, 1,8 the Boryong type predominates in the southern part of South Korea. 4,9 In addition, Kato, Neimeng-65, and Kawasaki genotypes have been identified in South Korea. 10 Although a prior study reported that the Boryong genotype rather than the Karp genotype predominated on Jeju Island, 7 we found that the Taguchi type was also common on Jeju Island.…”
mentioning
confidence: 99%
“…Although the Gilliam and Karp serotypes are reportedly more common in the central part, 1,8 the Boryong type predominates in the southern part of South Korea. 4,9 In addition, Kato, Neimeng-65, and Kawasaki genotypes have been identified in South Korea. 10 Although a prior study reported that the Boryong genotype rather than the Karp genotype predominated on Jeju Island, 7 we found that the Taguchi type was also common on Jeju Island.…”
mentioning
confidence: 99%
“…These cases were associated with age (Ն60 years), presentation without eschar, and laboratory findings such as white blood cell counts of Ͼ10,000/mm 3 and serum albumin levels of Յ3.0 g/dl. In a multicenter study conducted in the Republic of Korea, Park et al (12) reported that 10% of eschar-positive scrub typhus patients had central nervous system, respiratory, cardiac, or renal complications or septic shock. In the present study, complicated scrub typhus was observed in 28.1% of scrub typhus patients and 35% of hospitalized scrub typhus patients, consistent with the findings of previous studies (10 to 43%) (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study conducted in the Republic of Korea, Park et al (12) reported that 10% of eschar-positive scrub typhus patients had central nervous system, respiratory, cardiac, or renal complications or septic shock. In the present study, complicated scrub typhus was observed in 28.1% of scrub typhus patients and 35% of hospitalized scrub typhus patients, consistent with the findings of previous studies (10 to 43%) (11,12). Our results, as well as data from previous studies, show that complications in patients with scrub typhus are not uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations